Partial lateral corpectomy associated with pediculectomy to treat extradural chondroma in a dog: technique description - Marinho, Paulo Vinícius Tertuliano; Zani, Carolina Camargo; Jark, Paulo César [UNESP]; Minto, Bruno Watanabe [UNESP]; Costa, Mirela Tinucci (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
This study aimed to describe in detail the surgical technique of partial lateral corpectomy (PLC) associated with pediculectomy to treat an in vitro extradural chondroma. A 12-year old female Cocker Spaniel was seen in the hospital with proprioceptive ataxia of hind limbs associated with extradural compression between the 1st and 2nd lumbar vertebrae. The owner opted for euthanasia since the patient's condition changed due to simultaneous illnesses that culminated in a poor prognosis. The patient's body was formally ceded to perform experimental spinal decompression. The technique was effective to completely remove the epidural mass with minimal manipulation of the spinal cord.

Objetivou-se descrever detalhadamente a técnica cirúrgica de corpectomia lateral parcial associada à pediculectomia no tratamento de um condroma extradural in vitro. Uma cadela de 12 anos de idade, raça Cocker Spaniel, foi atendida com ataxia proprioceptiva dos membros pélvicos associada à compressão extradural entre a primeira e a segunda vértebras lombares. Devido a alterações secundárias decorrentes de afecções concomitantes que culminavam em um prognóstico desfavorável, o proprietário optou pela eutanásia do paciente, e o cadáver foi formalmente cedido para realização de descompressão medular experimental. A técnica utilizada foi eficaz na remoção completa da massa extradural, com mínima manipulação da medula espinhal.
Corpectomia lateral parcial associada à pediculectomia no tratamento de condroma extradural em um cão: descrição da técnica
Keywords: cão; compressão medular; neoplasias extradurais; neurocirurgia; dog; cord compression; extradural spinal tumors; neurosurgery